(untitled) (Damu Journal of Sport Sciences, 2025)
The research problem revolved around the possibility of achieving high performance figures. Here lies the great importance of using modern scientific methods and means in training, in order to develop the players' abilities and elevate them to the highest levels of athletic performance. The researchers used interval training and repetition training using (varied) wave intensities, diversifying the methods and techniques used, as well as using psychophysiological programs (psychological skills . The research sample was selected from weightlifters with special needs in the Holy Karbala Paralympic Committee. (7) players were chosen to represent the sample intentionally. The procedures for preparing the exercises were: (Physical-Psychological) according to some physical and psychophysiological variables with high and medium weights and intensities, and diversifying between them using the official bar. The researcher used the single-group experimental method with pre- and post-tests. The researcher found differences in the development rates between the pre- and post-tests of the research group in the psychophysical program and some physical and psychophysiological variables, and the performance of the bench press lift for players with special needs.